Remote outcomes in patients with cardiovascular diseases in outpatient practice: data from a 10-year follow-up within the RECVAZA registry - M. M. Luk'yanov; S. Yu. Martsevich; S. S. Yakushin; E. Yu. Andreenko; K. G. Pereverzeva; A. N. Kozminsky; E. A. Pravkina; V. G. Klyashtorny; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2025)
Aim. To evaluate outcomes over 10-year follow-up and risks of adverse events in patients with cardiovascular disease (CVD) within the outpatient registry.Material and methods. In the RECVAZA outpatient registry based on 3 Ryazan clinics, 3690 patients with CVD (age, 66,1±12,9 years; men, 28,0%) were observed. For 2012-2023 (follow-up, 8,2±3,3 years), the following outcomes were assessed: death, myocardial infarction (MI), stroke, hospitalization for CVD. Information on outcomes was obtained from medical records, surveys, electronic databases.Results. Over 10 years, 1595 patients (43,2%) died, 51% of whom died from CVD and 12% from cancer. The highest proportion of deaths was among patients with prior stroke (69,7%) and MI (61,5%) before inclusion in the registry, a combination of hypertension (HTN), coronary artery disease (CAD), heart failure (HF), atrial fibrillation (AF) — 79%, age ≥80 years — 85,9%. The highest all-cause and cardiovascular death risk was associated with age (hazard ratio (HR))=1,06 and HR=1,07; p<0,001); male sex (HR=1,70 and HR=1,62; p<0,001); prior stroke (HR=1,86 and HR=2,13; p<0,001); type 2 diabetes (HR=1,55 and HR=1,67; p<0,001); low hemoglobin level (HR=1,66 and HR=1,72; p<0,001); smoking (HR=1,51; p=0,001 and HR=1,72; p=0,003), respectively. The risk of MI was associated to the greatest extent with male sex and prior MI (HR=1,77 and HR=2,61; p<0,001), while the risk of stroke — with AF and prior stroke (HR=1,65 and 3,78; p<0,001) and systolic blood pressure <110 mm Hg (HR=2,72; p=0,01). Hospitalization for CVD no more than once per 2 years was associated with a lower risk of death (1,9 times), a higher frequency — with a higher risk (1,6 times).Conclusion. Over 10-year follow-up, 43,2% of patients with CVD died. The highest death rate was in patients with a history of stroke and MI, diabetes, with a combination of HTN, CAD, HF and AF, low hemoglobin levels. Hospitalization for CVD no more than once per 2 years was prognostically favorable, but with a higher frequency it was associated with an increased risk of death.